Utility of CDC Screening Guidelines and Autopsy Findings in Identifying Decedents Who Die of SARS-CoV-2 Infection. (4th June 2021) - Konopka, Kristine E.; Nguyen, Teresa; Hlavaty, Leigh; Rayes, Omar; Schmidt, Carl J.; Dahl, Julia; Myers, Jeffrey L.
Abstract: We assess the utility of a Centers for Disease Control and Prevention (CDC) guidelines-based coronavirus disease 2019 (COVID-19) screening checklist for postmortem severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) surveillance, detailing the relationship between the histologic findings at autopsy and attribution of death to COVID-19. SARS-CoV-2 nasopharyngeal swabs were collected at the time of autopsy in all "checklist-positive" decedents. Additional "checklist-negative" decedents were randomly tested daily. Lung slides were blindly reviewed by 3 pathologists, assessing for the presence of diffuse alveolar damage (DAD) and other findings. Sixteen decedents had positive postmortem SARS-CoV-2 nasopharyngeal swabs and underwent complete autopsies. Seven decedents had positive screening checklists. Of these, 4 had DAD and 1 had COVID-19–associated thromboembolic disease. Of the 9 decedents with negative screening checklists, 2 had DAD, but only 1 was attributed to COVID-19; the other was likely drug related. Acute bronchopneumonia was the second most common finding, and aspiration was the likely etiology in cases without concomitant DAD. COVID-19–related DAD was identified more commonly in decedents who screened positive by CDC checklist, but false-negatives did occur. Medical examiner offices should maintain a low threshold for random testing of decedents even when COVID-19 is not suspected.